Prescription criteria and effects of explosive strength training in indoor soccer players: a systematic review - Ana Belén Guzmán; Rubén Vidal-Espinoza; Luis Urzua-Alul; Luis Felipe Castelli Correia de Campos; José Fuentes-López; Camilo Urra-Albornoz; Marco Cossio-Bolaños; Rossana Gomez-Campos (PAGEPress Publications, 2024)
Explosive strength is fundamental in the performance of athletes. The objective is to identify the criteria used for the prescription of Explosive Strength Training (EST) and to verify the changes it produces in futsal players. A systematic review of studies analyzing the criteria used for the prescription of explosive strength training was conducted in PubMed/MEDLINE and Scielo, considering the period between 2017 and 2023. The search strategy used the terms: players, Futsal, Futsal training, strength, physical exercise, explosive strength, intervention, experimental study. Data extraction included: year of publication, country, sample, protocol performed (content and activity developed, duration, intensity, frequency, total weeks). A total of six studies were identified. Fifty percent of the studies were developed in Brazil, the others in Italy, Spain and Portugal. Five studies applied a training of 2 sessions per week and one indicated 2-3 sessions. Three studies describe the training sessions (study 1: 15-30 minutes, study 2: 20-25 minutes, study 3: 1 hour). Five studies used 1RM and one study used subjective perception of exertion (PSE). The contents of the interventions were varied, from squats with weights, accelerations and decelerations, leg press, leg extension, plyometrics. The training criteria for explosive strength were: intensity controlled by a 1RM, frequency of 2 to 3 sessions per week, duration of 15 to 30 minutes per session and the training contents were varied. These results suggest positive changes in CMJ, increasing explosive strength from ∼2.0 to 4.6 cm (5.8 to 13.7%). These findings highlight the need to develop a more standardized protocol to optimize the benefits of explosive strength training in this athletic population.